MANAJEMEN MUTU PENDIDIKAN TERHADAP PENERAPAN PROGRAM PEMBELAJARAN FULL DAY SCHOOL - Hernawati Hernawati; Abdul Aziz Muslimin; Sumiati Sumiati (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This Study aimed to determine the application of quality management of the full day school program which included three stategis: planning, impelementation and evaluation of Full Day School learning program, besides that its implementation also emphasized the implementation of school programns and learning activities, starting from the legal basis for implementation, the process of implementation, learning schedules and supporting facilities in the implementation of full day school. This study used a qualitative approach with the application of quality management to the implementation of the full day school program. Data collection techniques were trough observation, interviews and documentation. To check the validity of the data, triangulation techniques and data analysis techniques were used and then carried out by unitization, categorization, and data interpretation. The results of this study indicated that: First, the quality manajement for the implementation of full day school was very good, this can be seen from the schools that got A (Excellent) Accreditation Institution with a score 91 and the increase in the quantity of prospective students every year. Teacher professionalism was increasing and always creating varied and innovative learning. Secondly, the full day school learning program implemented at SMP Muhammadiyah 1 Makassar was good, starting from setting the study schedule, teaching and learning activities. This can be seen from the teaching and learning process activities that run systematically, Islamic habituation and environmental activities to form positive characters and attitudes for students, varied and innovative teaching and learning activities, and self development activities (extracurricular activities) that enabled to make student achievement increase both in the academic and non academic fields and the output of students who able to compete with other schools to get admission at reputable schools at the next levelof education